Impacts and correction of potassium deficiency in no-till and strip-till soybean and corn production - Blocker, Shannon M. (Kansas State University, 2009)
This study was initiated to determine if potassium (K) deficiencies seen in soybeans (Glycine max (L.) Merr.) under no-till and strip-till production systems are impacting soybean yields, and if so, what fertilizer application practices including: rate of K application; broadcast or deep band methods of application; and the use of starter fertilizer at planting; could be used to correct the problem. The residual impacts of K fertilization and placement were also evaluated on corn (Zea mays L.) grown in rotation with soybeans. This research was conducted on-farm in cooperation with local producers. Soybeans sites in 2007 were near Harris, Ottawa and Westphalia, Kansas with corn planted in 2008 at the sites near Ottawa and Westphalia. Soybean sites in 2008 were located near Ottawa and Welda, Kansas. Selected sites were generally near or below the current soil test K critical level of 130 mg per kg extractable K, based on sampling histories provided by the cooperators. Sampling in the spring of 2007 confirmed these soil test (ST) K levels. Soybean leaf tissue potassium levels in 2007 were less than the critical level of 17 mg per kg in the unfertilized control plots, and were significantly greater when potassium fertilizer was deep banded or a high-rate of K fertilizer was broadcast. No significant difference in yield of soybeans due to K fertilization was seen, likely due to significant water stress during the grain fill period, which severely limited soybean yield in 2007. Soil test K levels at all the research sites increased dramatically between 2007 and 2008, even where no K was applied. Different weather conditions experienced these two years may have contributed to this occurrence. No residual impacts of K fertilization in 2007 on soybeans were seen in soil tests, corn leaf tissue K levels or corn yield in 2008. Soybean sites in 2008 also showed a dramatic increase in K ST levels in 2008 as compared to farmer records. No effects of K fertilization on soybean growth or yield were seen in 2008. The 2008 Ottawa soybean site had very low P soil tests. A significant response to P fertilization contained in the starter treatments was observed. This suggests that the dominant farmer practice of applying P and K fertilizer to corn, and not applying fertilizer directly to soybeans, even at low soil test levels, may not be supplying adequate P to soybeans, and is likely costing farmers yields and profits.
Keywords: Potassium; Fertilizer placement; Soybeans; Residual fertilization; Deep band; Starter; Agriculture, Agronomy (0285); Agriculture, Soil Science (0481)